2009
DOI: 10.1128/ec.00298-08
|View full text |Cite
|
Sign up to set email alerts
|

Towards New Antifolates Targeting Eukaryotic Opportunistic Infections

Abstract: Trimethoprim, an antifolate commonly prescribed in combination with sulfamethoxazole, potently inhibits several prokaryotic species of dihydrofolate reductase (DHFR). However, several eukaryotic pathogenic organisms are resistant to trimethoprim, preventing its effective use as a therapeutic for those infections. We have been building a program to reengineer trimethoprim to more potently and selectively inhibit eukaryotic species of DHFR as a viable strategy for new drug discovery targeting several opportunist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…Cryptosporidium is remarkably resistant to antifolates, a mainstay of treatment against other apicomplexans, and this resistance has been attributed to differences in the target enzyme dihydrofolate reductase-thymidylate synthase (DHFR-TS) 24 . However, Cryptosporidium is unique among apicomplexans in that it acquired a thymidine kinase (TK) by horizontal gene transfer from bacteria 25 .…”
mentioning
confidence: 99%
“…Cryptosporidium is remarkably resistant to antifolates, a mainstay of treatment against other apicomplexans, and this resistance has been attributed to differences in the target enzyme dihydrofolate reductase-thymidylate synthase (DHFR-TS) 24 . However, Cryptosporidium is unique among apicomplexans in that it acquired a thymidine kinase (TK) by horizontal gene transfer from bacteria 25 .…”
mentioning
confidence: 99%
“…However, given that Dfr1p is present in humans and fairly well conserved between mammals and fungi, selectivity is likely to be an issue. Interestingly, Anderson and colleagues (18,53) described trimethoprim derivatives with an extended central linker with dramatically enhanced potency against C. glabrata DHFR. However, despite exhibiting selective inhibition of the fungal enzyme over the human enzyme in cell-free biochemical assays, toxicity to mammalian cells remained an issue (54).…”
Section: Discussionmentioning
confidence: 99%
“…In its reduced form, tetrahydrofolate (THF) is an essential coenzyme for a number of cellular enzymes, serving as a carrier for the transfer of one-carbon (1C) units as well as their interconversion between various oxidation states (18). THF is required for the synthesis of dTMP, purines, and methionine, as well as a multitude of other important metabolites.…”
mentioning
confidence: 99%
“…For example, mutations in the BaDHFR active site revealed that the polar character of Y102 negatively impacts the enzyme’s affinity with TMP and the propargyl-linked compounds, thus aiding in elucidating one factor of the enzyme’s innate resistance to TMP. While polar propargylic substitutions may appear appealing, such substitutions have been shown in other species to have a negative impact on cell permeability 17 . Mutational studies also helped further interpret information gathered from structure-based drug design studies.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of mutant BaDHFR enzymes also helped further analyze the complex SAR data to understand the role of substituents on the propargyl linker of the lead compounds, as well as the effect of substitution patterns around the aryl ring. Currently, inhibitor development has been directed towards a methyl substituent on the propargyl bridge due to the efficacy seen in other DHFR species such as SaDHFR, C. hominus DHFR, and C. glabrata DHFR 6a, 7b, 1718 . These mutational studies indicate that a propargylic hydrogen would be a more favorable substituent for BaDHFR.…”
Section: Discussionmentioning
confidence: 99%